Memorizing Qur’an and Mathematics Achievement - Nuqthy Faiziyah (Department of Mathematics Education University of Muhammadiyah Malang, 2018)
The aim of this research is to know the correlation between memorizingQur‘an and mathematics learning achievement. It is a quantitative researchusing linear regression. The sample was taken by purpose sampling technicand an elementary school in Sragen was chosen. The data source was adocument of the mathematics subject mark and the number surahmemorized. The result shows that there is a correlation between memorizingQur‘an and mathematics learning achievement. The regression linear modelwas able to be built. The coefficient of regression is 1.024. This shows thatmemorizing one surah of Qur‘an more would make the mathematicslearning achievement increases at 1.024 point. The coefficient ofdetermination is 0.365. The conclusion is that memorizing Qur‘an hascontribution to mathematics learning achievement This electronic documentis a ―live‖ template and already defines the components of your paper [title,text, heads, etc.] in its style sheet.